Development Of Electrical Motor Control Learning Media As Learning Support For Electrical Power Installation Courses In The Department Of Electrical Engineering - Supari Muslim; Tri Wrahatnolo; Sri Handayani; Erina Rahmadyanti; Nita Kusumawati; Joko Joko (Universitas Negeri Makassar, 2018)
Learning media is everything that can channel the message of learning resources in a planned manner, to create a conducive learning environment, where the recipient can carry out the learning process effectively and efficiently. Vocational learning must be effective in meeting basic objectives to prepare vocational graduates to be ready to work. Thus, it is an assignment for lecturers whose function is to prepare vocational teacher candidates. The question that arises is